Proton exchange membrane, preparation method and application thereof
By using the lamination arrangement of perfluorosulfonic acid resin particles, crosslinking agents and solvents and irradiation crosslinking treatment methods in the preparation of the proton exchange membrane, the problem that proton exchange membranes in the prior art are difficult to have high mechanical strength and high proton conductivity, and efficient energy conversion and stability are achieved.
Patent Information
- Application Number
- CN202411974341.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
It is difficult to produce a proton exchange membrane with high mechanical strength and high proton conductivity in the prior art, resulting in limited energy conversion efficiency and stability of the proton exchange membrane fuel cell.
Using a method of preparing a proton exchange membrane, a resin slurry is formed by mixing perfluorosulfonic acid resin particles, a crosslinking agent and a solvent, and stacking it between the base film layer and the organic polymer film layer, and then irradiated crosslinking treatment is performed under an inert atmosphere to form a stable crosslinking network.
The proton exchange membrane has high mechanical strength and high proton transmission efficiency, which improves the energy conversion efficiency and stability of the proton exchange membrane fuel cell.
Smart Images

Figure CN119752233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of proton exchange membrane fuel cells, and in particular to a proton exchange membrane, a preparation method and application thereof. Background Art
[0002] Hydrogen fuel cells have become a highly anticipated research direction in the field of green energy due to their high energy conversion efficiency, zero emissions and renewable energy. As a key core component of hydrogen fuel cells, the performance of proton exchange membranes is directly related to the overall performance, operating efficiency and service life of the battery. In practical applications, proton exchange membranes need to have high proton conduction efficiency, good chemical stability and mechanical properties.
[0003] In the traditional process of preparing proton exchange membranes, expanded polytetrafluoroethylene (e-PTFE) is introduced as a reinforcement layer to construct a composite membrane structure, thereby enhancing the mechanical strength of the proton exchange membrane. However, the hydrophobic molecular chain of e-PTFE limits its ability to conduct protons. When its proportion in the composite membrane is too high, the conductivity of the composite membrane will decrease, thereby affecting the proton transmission efficiency.
[0004] Existing document (publication number CN1482161A) discloses the preparation of a novel cross-linkable polyaryletherketone sulfonated membrane, wherein the sulfide-containing polymer FKOSOKF or FKKOSOKKF is dissolved in 98% concentrated sulfuric acid or fuming sulfuric acid with 50% free SO3 at 20-50°C, stirred, and the amount of concentrated sulfuric acid or fuming sulfuric acid is 10-40mL / g, and the sulfonic acid group is introduced into the polymer main chain structure, which can significantly improve its water content and proton conductivity. On the other hand, the cross-linked network is formed by the sulfide bond under the condition of electron beam irradiation to solve the contradiction of the decrease of its mechanical strength under the condition of high sulfonation degree, thereby solving the problem of balancing proton conduction and mechanical strength. However, in order to improve the proton conduction ability of the polyaryletherketone sulfonated membrane, the above method introduces a large number of sulfonic acid side groups, which destroys the structure of the polyaryletherketone main chain that guarantees the strength of the material, resulting in the inability of the membrane to have both excellent proton conduction performance and high mechanical strength.
[0005] In summary, researching and developing a proton exchange membrane with high mechanical strength and high electrical conductivity and a preparation method thereof are of great significance to improving the energy conversion efficiency and stability of proton exchange membrane fuel cells. Summary of the invention
[0006] The main purpose of the present invention is to provide a proton exchange membrane, a preparation method and application thereof, so as to solve the problem that it is difficult to prepare a proton exchange membrane with both high mechanical strength and high proton conductivity by the preparation process in the prior art.
[0007] In order to achieve the above object, the present invention provides a method for preparing a proton exchange membrane, which comprises: step S1, mixing perfluorosulfonic acid resin particles, a cross-linking agent and a solvent to obtain a resin slurry; the cross-linking agent is a compound represented by general formula (I): Wherein, R1 is selected from C1-C4 straight chain or branched chain alkylene, or a connecting bond; R2 is selected from hydrogen or a straight or branched alkyl group of C1 to C4; n is any integer from 1 to 4; step S2, applying a portion of the resin slurry to one side surface of the base film layer to obtain a first wet film, covering the surface of the first wet film with a layer of organic polymer film layer, and obtaining a first laminated structure after a first drying; the first laminated structure includes a base film layer, a first resin slurry layer and an organic polymer film layer stacked in sequence; step S3, applying another portion of the resin slurry to the side surface of the organic polymer film layer away from the base film layer to obtain a second wet film, and obtaining a second laminated structure after a second drying; the second laminated structure includes a base film layer, a first resin slurry layer, an organic polymer film layer and a second resin slurry layer stacked in sequence; step S4, under an inert atmosphere, irradiating and cross-linking the second laminated structure, and after completion, peeling off the base film layer to obtain a proton exchange membrane; the proton exchange membrane includes a first resin layer, an organic polymer film layer and a second resin layer stacked in sequence.
[0008] Further, R1 is methylene, ethylene, or a connecting bond; preferably, n is 1 or 2, and R2 is hydrogen; preferably, n is 3, and R2 is a C1-C4 straight-chain alkyl group, preferably a methyl group or an ethyl group; preferably, n is 4, and R1 is a methylene group.
[0009] Further, the cross-linking agent is selected from one or more of the following compounds:
[0010]
[0011]
[0012] Furthermore, the weight percentage of the cross-linking agent in the resin slurry is 1 to 10 wt %; preferably, the weight ratio of the perfluorosulfonic acid resin particles to the solvent is 1:(1 to 100); preferably, the weight ratio of the perfluorosulfonic acid resin particles to the cross-linking agent is (1 to 30):1; preferably, the ion exchange equivalent of the perfluorosulfonic acid resin particles is 500 to 1500 g / mol, and the average particle size is 50 to 500 mm; preferably, the solvent is selected from water and / or alcohol solvents; more preferably, the alcohol solvent is selected from one or more of the group consisting of ethanol, isopropanol, n-propanol, n-butanol and n-hexanol.
[0013] Further, the viscosity of the resin slurry is 10-100 mPa·s. Preferably, in step S2, the thickness of the first wet film is 70-150 μm; preferably, in step S3, the thickness of the second wet film is 70-150 μm.
[0014] Furthermore, the organic polymer membrane layer is a porous membrane; preferably, the porosity of the organic polymer membrane layer is 50-90%, the average pore size is 80-300 μm, and the thickness is 4-15 μm; preferably, the material of the organic polymer membrane layer is expanded polytetrafluoroethylene.
[0015] Furthermore, the thickness of the base film layer is 50-200 μm; preferably, the material of the base film layer is selected from one or more of the group consisting of polyethylene terephthalate, polyimide and polyphenylene sulfide.
[0016] Furthermore, in step S4, an electron beam or gamma ray is used for irradiation crosslinking treatment; preferably, an electron beam is used for irradiation crosslinking treatment, the irradiation dose of the irradiation crosslinking treatment is 1 to 50 KGy, the electron beam energy is 0.8 to 2 MeV, and the electron beam current is 5 to 20 mA.
[0017] Furthermore, in step S1, the mixing temperature is 25-100°C and the mixing time is 0.5-5h; preferably, stirring is performed during the mixing process at a stirring rate of 200-1000rpm.
[0018] Furthermore, in step S2, the first drying temperature is 60-200°C, and the time is 1-20 min; preferably, in step S3, the second drying temperature is 60-200°C, and the time is 1-20 min.
[0019] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a proton exchange membrane, which is prepared by the preparation method of the proton exchange membrane provided by the present application. The proton exchange membrane comprises a first resin layer, an organic polymer membrane layer and a second resin layer stacked in sequence; the tensile strength of the proton exchange membrane in the transverse direction is 49-76MPa, the elastic modulus in the transverse direction is 418-873MPa, the tensile strength in the longitudinal direction is 50-78MPa, the elastic modulus in the longitudinal direction is 446-880MPa, and the conductivity is 0.091-0.251S / cm.
[0020] Furthermore, the thickness of the proton exchange membrane is 8 to 15 μm.
[0021] Another aspect of the present invention provides an application of the proton exchange membrane provided in the present application in a proton exchange membrane fuel cell.
[0022] By applying the technical solution of the present invention, the preparation method of the proton exchange membrane provided by the present application introduces a compound represented by the general formula (I) as a crosslinking agent when preparing the resin slurry, wherein the ester structure contained in the crosslinking agent is hydrophilic, and the presence of the hydrophilic group can inhibit the aggregation of perfluorosulfonic acid resin particles in the solvent, improve the dispersibility and stability of the resin slurry, reduce the surface tension of the resin slurry on the surface of the organic polymer membrane layer, and improve its wetting effect with the base membrane layer and the organic polymer membrane layer, thereby forming a more uniform and stable membrane layer structure. In addition, the unsaturated bonds (such as carbon-carbon double bonds) in the above crosslinking agent can undergo free radical crosslinking reaction under the irradiation crosslinking treatment of step S4, and at the same time combine with the active sites on the perfluorosulfonic acid resin to form a stable crosslinking network, thereby improving the mechanical strength (such as tensile strength and elastic modulus) and stability of the proton exchange membrane. At the same time, the presence of hydrophilic groups can also enhance the wettability of the proton exchange membrane, thereby promoting the conduction of protons and improving the conductivity of the proton exchange membrane, so that the proton exchange membrane made therefrom has high mechanical strength and high proton transfer efficiency. In addition, the base membrane layer provides a flat support platform, which facilitates the coating and molding of the resin slurry; the introduction of the organic polymer membrane layer can also improve the mechanical strength and stability of the proton exchange membrane. The application of the above-mentioned proton exchange membrane in proton exchange membrane fuel cells can improve the energy conversion efficiency and stability of proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 A schematic diagram of a first stacked structure in one embodiment of the present application is shown;
[0025] Figure 2 A schematic diagram of a first stacked structure in one embodiment of the present application is shown;
[0026] Figure 3 A schematic diagram of the proton exchange membrane structure in one embodiment of the present application is shown.
[0027] The above drawings include the following reference numerals:
[0028] 10. Base film layer; 20. Organic polymer film layer; 30. First resin slurry layer; 31. First resin layer; 40. Second resin slurry layer; 41. Second resin layer. DETAILED DESCRIPTION
[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0030] As described in the background technology, the existing proton exchange membrane preparation process has the problem of difficulty in preparing a proton exchange membrane with both high mechanical strength and high conductivity. In order to solve the above technical problems, the present application provides a method for preparing a proton exchange membrane, the preparation method comprising: step S1, mixing perfluorosulfonic acid resin particles, a crosslinking agent and a solvent to obtain a resin slurry; the crosslinking agent is a compound represented by general formula (I):
[0031] Wherein, R1 is selected from C1-C4 straight chain or branched chain alkylene, or a connecting bond; R2 is selected from hydrogen or a C1-C4 straight or branched alkyl group; n is any integer from 1 to 4; step S2, applying a portion of the resin slurry to one side of the base film layer 10 to obtain a first wet film, and covering the surface of the first wet film with an organic polymer film layer 20, and obtaining a first laminated structure after a first drying; Figure 1 As shown, the first laminated structure includes a base film layer 10, a first resin slurry layer 30 and an organic polymer film layer 20 which are stacked in sequence; in step S3, another part of the resin slurry is applied to a surface of the organic polymer film layer 20 away from the base film layer 10 to obtain a second wet film, and a second laminated structure is obtained after a second drying; as shown Figure 2 As shown, the second laminated structure includes a base film layer 10, a first resin slurry layer 30, an organic polymer film layer 20 and a second resin slurry layer 40 which are stacked in sequence; step S4, in an inert atmosphere, the second laminated structure is subjected to radiation cross-linking treatment, and after completion, the base film layer 10 is peeled off to obtain a proton exchange membrane; Figure 3 As shown, the proton exchange membrane includes a first resin layer 31, an organic polymer membrane layer 20 and a second resin layer 41 which are stacked in sequence.
[0032] By applying the technical solution of the present invention, the preparation method of the proton exchange membrane provided by the present application introduces the compound shown in the general formula (I) as a crosslinking agent when preparing the resin slurry, wherein the ester structure contained in the crosslinking agent is hydrophilic, and the presence of the hydrophilic group can inhibit the aggregation of perfluorosulfonic acid resin particles in the solvent, improve the dispersibility and stability of the resin slurry, reduce the surface tension of the resin slurry on the surface of the organic polymer membrane layer 20, and improve its wetting effect with the base membrane and the organic polymer membrane, thereby forming a more uniform and stable membrane layer structure. In addition, the unsaturated bonds (such as carbon-carbon double bonds) in the above crosslinking agent can undergo free radical crosslinking reaction under the irradiation crosslinking treatment of step S4, and at the same time combine with the active sites on the perfluorosulfonic acid resin, thereby forming a stable crosslinking network, thereby improving the mechanical strength (such as tensile strength and elastic modulus) and stability of the proton exchange membrane. At the same time, the presence of the hydrophilic group can also enhance the wettability of the proton exchange membrane, thereby promoting the conduction of protons and improving the conductivity of the proton exchange membrane, thereby making the prepared proton exchange membrane have a high mechanical strength and a high proton transfer efficiency. In addition, the base membrane layer 10 provides a flat support platform, which is convenient for the coating and molding of the resin slurry; the introduction of the organic polymer membrane layer 20 can also improve the mechanical strength and stability of the proton exchange membrane. The application of the above-mentioned proton exchange membrane in a proton exchange membrane fuel cell can improve the energy conversion efficiency and stability of the proton exchange membrane fuel cell.
[0033] In a preferred embodiment, R1 is methylene, ethylene, Compared with other structures, the cross-linking agent with the above structure is conducive to the introduction of more suitable hydrophilic groups, thereby reducing the surface tension of the resin slurry on the surface of the organic polymer membrane layer 20, improving its wetting effect with the base membrane layer 10 and the organic polymer membrane layer 20, and forming a more stable and uniform membrane structure. At the same time, it is also conducive to improving the wettability of the proton exchange membrane, thereby promoting the conduction of protons and improving the conductivity of the proton exchange membrane; on the other hand, it is conducive to enhancing the binding effect between the cross-linking agent and the active sites on the perfluorosulfonic acid resin, thereby forming a more stable cross-linking network, thereby improving the mechanical strength and stability of the proton exchange membrane.
[0034] In order to further reduce the surface tension of the resin slurry on the surface of the organic polymer membrane layer 20, improve its wetting effect with the base membrane layer 10 and the organic polymer membrane layer 20, thereby further improving the proton transfer efficiency of the proton exchange membrane, and at the same time to further enhance the binding effect between the cross-linking agent and the active sites on the perfluorosulfonic acid resin, further form a more stable cross-linked network, thereby further improving the mechanical strength and stability of the proton exchange membrane, preferably, n is 1 or 2, R2 is hydrogen; or, n is 3, R2 is a straight-chain alkyl group of C1 to C4, preferably a methyl or ethyl group; or, n is 4, and R1 is a methylene group.
[0035] In a preferred embodiment, the cross-linking agent includes but is not limited to one or more of the following compounds:
[0036]
[0037] Compared with other types, the use of the above-mentioned types of cross-linking agents is beneficial to improving the reaction efficiency of the free radical cross-linking reaction occurring under the radiation cross-linking treatment, and is beneficial to forming a more stable cross-linking network, thereby helping to improve the mechanical strength and stability of the proton exchange membrane; on the other hand, it is beneficial to introduce more suitable hydrophilic groups, thereby helping to reduce the surface tension of the resin slurry on the surface of the organic polymer membrane layer 20, improving its wetting effect with the base membrane layer 10 and the organic polymer membrane layer 20, and helping to form a more stable and uniform membrane layer structure, and at the same time, it is also beneficial to improve the wettability of the proton exchange membrane, thereby promoting the conduction of protons and improving the electrical conductivity of the proton exchange membrane.
[0038] In a preferred embodiment, the weight percentage of the crosslinking agent in the resin slurry is 1-10wt%. The weight percentage of the crosslinking agent in the resin slurry includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the crosslinking density of the first resin layer 31 and the second resin layer 41, thereby forming a more stable crosslinked network structure, thereby improving the mechanical strength and stability of the proton exchange membrane; on the other hand, it is beneficial to introduce a more appropriate amount of hydrophilic groups, which is beneficial to suppress the reduction of proton transfer efficiency caused by excessive crosslinking agent, thereby improving the proton transfer efficiency while improving the mechanical strength of the proton exchange membrane.
[0039] In order to form a more stable cross-linked network structure, further improve the mechanical strength and stability of the proton exchange membrane, and further improve the proton transfer efficiency of the proton exchange membrane, preferably, the weight ratio of the perfluorosulfonic acid resin particles to the cross-linking agent is (1-30):1.
[0040] In a preferred embodiment, the weight ratio of the perfluorosulfonic acid resin particles to the solvent is 1:(1-100). The weight ratio of the perfluorosulfonic acid resin particles to the solvent includes but is not limited to the above range, and limiting it within the above range is conducive to improving the dispersibility and stability of the perfluorosulfonic acid resin particles, and is conducive to inhibiting the agglomeration of the perfluorosulfonic acid resin particles in the solvent, thereby facilitating improving the efficiency of the subsequent radiation cross-linking treatment.
[0041] Ion exchange equivalent (EW value) refers to the number of moles of exchangeable protons that a unit weight of resin can provide, and the EW value is used to evaluate the ion exchange capacity of the resin. In a preferred embodiment, the ion exchange equivalent of the perfluorosulfonic acid resin particles is 500 to 1500 g / mol. The EW value of the perfluorosulfonic acid resin particles includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the mechanical strength of the perfluorosulfonic acid resin particles while improving their ion exchange capacity, thereby helping to improve the mechanical strength and conductivity of the proton exchange membrane; on the other hand, it is beneficial to improve the dispersibility of the perfluorosulfonic acid resin particles and inhibit the agglomeration of the perfluorosulfonic acid resin particles, thereby helping to form a more evenly dispersed resin slurry.
[0042] In order to improve the dispersibility of the perfluorosulfonic acid resin particles and to obtain a more uniform resin slurry, in a preferred embodiment, the average particle size of the perfluorosulfonic acid resin particles is 50 to 500 mm.
[0043] In a preferred embodiment, the solvent includes but is not limited to water and / or alcohol solvents; preferably, the alcohol solvent includes but is not limited to one or more of the group consisting of ethanol, isopropanol, n-propanol, n-butanol and n-hexanol. Compared with other types, the use of the above types of solvents is conducive to improving the dispersibility and stability of the resin slurry, thereby facilitating the formation of a more stable film structure.
[0044] In order to improve the dispersion uniformity of the resin slurry, improve the coating uniformity, and facilitate obtaining a film layer with a suitable thickness, in a preferred embodiment, the viscosity of the resin slurry is 10 to 100 mPa·s.
[0045] In a preferred embodiment, in step S2, the thickness of the first wet film is 70 to 150 μm. The thickness of the first wet film includes but is not limited to the above range. Limiting it within the above range is conducive to obtaining a first resin slurry layer 30 with an appropriate thickness, which is conducive to suppressing the increase in proton transmission resistance caused by the first resin slurry layer 30 being too thick, and is also conducive to improving the efficiency of subsequent radiation cross-linking treatment to obtain the first resin layer 31, thereby facilitating improving the mechanical strength, stability and proton transmission efficiency of the proton exchange membrane.
[0046] In a preferred embodiment, in step S3, the thickness of the second wet film is 70 to 150 μm. The thickness of the second wet film includes but is not limited to the above range. Limiting it within the above range is conducive to obtaining a second resin slurry layer 40 with an appropriate thickness, which is conducive to suppressing the increase in proton transmission resistance caused by the second resin slurry layer 40 being too thick, and is also conducive to improving the efficiency of subsequent radiation cross-linking treatment to obtain a second resin layer 41, thereby facilitating improving the mechanical strength, stability and proton transmission efficiency of the proton exchange membrane.
[0047] In order to provide more proton transfer paths and reduce proton transfer resistance, and at the same time to make it easier for water molecules to penetrate and diffuse, improve the wettability of the proton exchange membrane, thereby promoting proton conduction and improving the conductivity of the proton exchange membrane, in a preferred embodiment, the organic polymer membrane layer 20 is a porous membrane.
[0048] In a preferred embodiment, the porosity of the organic polymer membrane layer 20 is 50-90%, the average pore size is 80-300 μm, and the thickness is 4-15 μm. The porosity, average pore size and thickness of the organic polymer membrane layer 20 include but are not limited to the above ranges. Limiting it within the above ranges is conducive to providing more proton transmission paths, reducing proton transmission resistance, and improving the wettability of the proton exchange membrane, thereby improving the conductivity of the proton exchange membrane; at the same time, the organic polymer membrane layer 20 with a suitable thickness is also conducive to improving the mechanical strength and stability of the proton exchange membrane.
[0049] In order to improve the chemical stability and mechanical strength of the organic polymer membrane layer 20, and thus further improve the mechanical strength and stability of the proton exchange membrane, in a preferred embodiment, the material of the organic polymer membrane layer 20 is expanded polytetrafluoroethylene (e-PTFE), which can be e-PTFE with model number 381208E1-1402 produced by Donaldson Company of the United States, or e-PTFE with model number SRM001-01 or SRM001-03 produced by Senrong New Material Technology Co., Ltd.
[0050] In a preferred embodiment, the thickness of the base film layer 10 is 50 to 200 μm. The thickness of the base film layer 10 includes but is not limited to the above range, and limiting it within the above range facilitates the coating and molding of the resin slurry.
[0051] In a preferred embodiment, the material of the base film layer 10 includes but is not limited to one or more of the group consisting of polyethylene terephthalate (PET), polyimide (PI) and polyphenylene sulfide (PPS). Compared with other types, the above-mentioned base film layer 10 materials have good chemical stability and mechanical strength, which is conducive to providing a more stable support platform, thereby facilitating the coating and molding of the resin slurry.
[0052] Electron beam irradiation is an irradiation process that uses an electron accelerator to accelerate electrons at high energy and directly or indirectly act on the target material. It has the advantages of adjustable energy, controllable dosage, fast processing speed, no pollution, and no generation of radioactive waste. Gamma ray irradiation is the use of gamma rays produced by radioactive isotopes to irradiate substances to cause various chemical reactions or physical changes. In a preferred embodiment, in step S4, an electron beam or gamma ray is used for irradiation cross-linking treatment. Compared with other methods, the above method is conducive to more accurately controlling the conditions of the irradiation cross-linking treatment, thereby helping to improve the efficiency of the irradiation cross-linking treatment, and then helping to improve the mechanical strength and stability of the proton exchange membrane.
[0053] In a preferred embodiment, an electron beam is used for radiation cross-linking treatment, and the radiation dose of the radiation cross-linking treatment is 1 to 50 KGy, the electron beam energy is 0.8 to 2 MeV, and the electron beam current is 5 to 20 mA. Compared with other ranges, limiting the radiation dose, electron beam energy and electron beam current of the radiation cross-linking treatment to the above range is conducive to improving the efficiency of the radiation cross-linking treatment, and is conducive to inhibiting the membrane layer structure from being damaged during the radiation cross-linking treatment, thereby helping to improve the mechanical strength and stability of the proton exchange membrane.
[0054] In a preferred embodiment, in step S1, the mixing temperature is 25-100° C. and the mixing time is 0.5-5 hours. The mixing temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the mixing efficiency and inhibiting the agglomeration of the perfluorosulfonic acid resin particles, thereby facilitating the obtaining of a more uniformly dispersed resin slurry.
[0055] In order to further improve the mixing efficiency and the dispersion uniformity of the resin slurry, preferably, stirring is performed during the mixing process, and the stirring rate is 200 to 1000 rpm.
[0056] In order to improve the removal rate of the solvent in the resin slurry, thereby facilitating the formation of a stable first resin slurry layer 30, in a preferred embodiment, in step S2, the first drying temperature is 60-200°C and the time is 1-20 minutes.
[0057] In order to improve the removal rate of the solvent in the resin slurry, thereby facilitating the formation of a stable second resin slurry layer 40, in a preferred embodiment, in step S3, the second drying temperature is 60-200°C and the time is 1-20 minutes.
[0058] The second aspect of the present application also provides a proton exchange membrane, such as Figure 3As shown, the proton exchange membrane includes a first resin layer 31, an organic polymer membrane layer 20 and a second resin layer 41 which are stacked in sequence, and is prepared by the above-mentioned proton exchange membrane preparation method provided in the present application.
[0059] The preparation method of the above-mentioned proton exchange membrane provided by the present application introduces the compound shown in general formula (I) as a cross-linking agent when preparing the resin slurry, wherein the ester structure contained in the cross-linking agent is hydrophilic, and the presence of the hydrophilic group can inhibit the aggregation of perfluorosulfonic acid resin particles in the solvent, improve the dispersibility and stability of the resin slurry, reduce the surface tension of the resin slurry on the surface of the organic polymer film layer 20, and improve its wetting effect with the base film layer 10 and the organic polymer film layer 20, thereby forming a more uniform and stable membrane layer structure. In addition, the unsaturated bonds (such as carbon-carbon double bonds) in the above-mentioned cross-linking agent can undergo free radical cross-linking reaction under the radiation cross-linking treatment of step S4, and at the same time combine with the active sites on the perfluorosulfonic acid resin to form a stable cross-linking network, thereby improving the mechanical strength (such as tensile strength and elastic modulus) and stability of the proton exchange membrane. At the same time, the presence of the hydrophilic group can also enhance the wettability of the proton exchange membrane, thereby promoting the conduction of protons and improving the conductivity of the proton exchange membrane, thereby making the proton exchange membrane made therefrom have high mechanical strength and high proton transfer efficiency. The application of the above-mentioned proton exchange membrane in proton exchange membrane fuel cells can improve the energy conversion efficiency and stability of proton exchange membrane fuel cells.
[0060] Under the conditions of 25°C and 50% RH, the tensile strength of the proton exchange membrane provided by the present application in the transverse direction (TD direction) is 49-76MPa, the elastic modulus in the transverse direction (TD direction) is 418-873MPa, the tensile strength in the longitudinal direction (MD direction) is 50-78MPa, and the elastic modulus in the longitudinal direction (MD direction) is 446-880MPa. Under the conditions of 80°C and 80% RH, the conductivity of the proton exchange membrane provided by the present application is 0.091-0.251S / cm. It can be seen from this that the proton exchange membrane prepared by the preparation method of the proton exchange membrane provided by the present application can have both high mechanical strength and high proton transfer efficiency. It should be noted that due to the particularity of the technical field of proton exchange membrane preparation and the limitations of existing test characterization methods, it is difficult to conduct a comprehensive quantitative characterization of the complex cross-linked structure in the proton exchange membrane obtained above, but experiments show that the proton exchange membrane obtained by the present application has higher mechanical strength and conductivity.
[0061] In a preferred embodiment, the thickness of the proton exchange membrane is 8 to 15 μm. The thickness of the proton exchange membrane includes but is not limited to the above range. Limiting it within the above range is conducive to improving the mechanical strength and stability of the proton exchange membrane, and is conducive to suppressing the increase of proton transfer resistance caused by excessive thickness of the membrane layer, thereby helping to improve the proton transfer efficiency of the proton exchange membrane.
[0062] The third aspect of the present application also provides an application of the above-mentioned proton exchange membrane provided by the present application in a proton exchange membrane fuel cell.
[0063] The proton exchange membrane prepared by the above-mentioned proton exchange membrane preparation method provided in the present application has both high mechanical strength and high proton transfer efficiency. Its application in proton exchange membrane fuel cells can improve the energy conversion efficiency and stability of proton exchange membrane fuel cells.
[0064] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0065] Example 1
[0066] A method for preparing a proton exchange membrane comprises the following steps:
[0067] (1) 14 g of perfluorosulfonic acid resin particles (Zhejiang Juhua Co., Ltd., E85L, EW value 900 g / mol, average particle size 50 mm) were mixed with 120 g of a mixed solvent consisting of water, ethanol and isopropanol, and stirred at 100° C. and 700 rpm for 2 h to obtain a resin solution, wherein the volume ratio of water, ethanol and isopropanol was 3:6:1;
[0068] (2) The chemical structure of the cross-linking agent in this embodiment is (purchased from Merck Sigma-Aldrich), wherein R1 is methylene, R2 is ethyl, and n is 3;
[0069] 1.34 g of the cross-linking agent was added to the resin solution obtained in step (1), and the mixture was stirred at 25° C. and 700 rpm for 30 min to obtain a resin slurry; wherein the weight percentage of the cross-linking agent in the resin slurry was 1 wt %, and the viscosity of the resin slurry was 35.4 mPa·s;
[0070] (3) The resin slurry prepared in step (2) is coated on one side of a polyethylene terephthalate (PET, purchased from Daicel) base film layer 10 with a thickness of 70 μm to obtain a wet film with a thickness of 100 μm; then a layer of expanded polytetrafluoroethylene (e-PTFE, Donaldson, 381208E1-1402) film with a thickness of 11 μm is covered on the surface of the resin slurry, the porosity of the e-PTFE film layer is 80%, and the average pore size is 170 μm, and then dried at 100° C. for 5 min to obtain a first laminated structure, as shown in FIG. Figure 1 As shown;
[0071] (4) coating the resin slurry obtained in step (2) on the surface of the e-PTFE film layer away from the PET base film layer 10 to obtain a wet film with a thickness of 80 μm; then drying at 160° C. for 8 min to obtain a second laminated structure, such as Figure 2 As shown;
[0072] (5) Under a nitrogen atmosphere, the second laminate structure obtained in step (4) is subjected to irradiation crosslinking treatment using an electron beam, wherein the temperature of the irradiation crosslinking treatment is 25° C., the irradiation dose is 30 KGy, the electron beam energy is 0.8 MeV, and the electron beam current is 10 mA. After the irradiation crosslinking treatment is completed, the bottom PET base film is peeled off to obtain a proton exchange membrane with a thickness of 12 μm; Figure 3 As shown, the proton exchange membrane includes a first resin layer 31, an organic polymer membrane layer 20 (e-PTFE membrane layer) and a second resin layer 41 which are stacked in sequence.
[0073] Example 2
[0074] The difference from Example 1 is that in step (2), the weight percentage of the cross-linking agent in the resin slurry is 2wt%, and the remaining steps are the same as Example 1.
[0075] Example 3
[0076] The difference from Example 1 is that in step (2), the weight percentage of the cross-linking agent in the resin slurry is 4wt%, and the remaining steps are the same as Example 1.
[0077] Example 4
[0078] The difference from Example 1 is that in step (2), the weight percentage of the cross-linking agent in the resin slurry is 10wt%, and the remaining steps are the same as Example 1.
[0079] Example 5
[0080] The difference from Example 1 is that in step (2), the weight percentage of the cross-linking agent in the resin slurry is 11wt%, and the remaining steps are the same as Example 1.
[0081] Example 6
[0082] The difference from Example 1 is that the chemical structure of the cross-linking agent used in step (2) of this example is: (purchased from Merck Sigma-Aldrich), where R1 is R2 is ethyl, n is 3; the remaining steps are the same as in Example 1.
[0083] Example 7
[0084] The difference from Example 1 is that the chemical structure of the cross-linking agent used in step (2) of this example is: (purchased from Merck Sigma-Aldrich), wherein R1 is methylene, R2 is H, and n is 2; the remaining steps are the same as in Example 1.
[0085] Example 8
[0086] The difference from Example 1 is that the chemical structure of the cross-linking agent used in step (2) of this example is: (purchased from Merck Sigma-Aldrich), wherein R1 is methylene and n is 4; the remaining steps are the same as in Example 1.
[0087] Example 9
[0088] The difference from Example 1 is that in step (5), the radiation dose of the radiation cross-linking treatment is 20 KGy, and the remaining steps are the same as Example 1.
[0089] Example 10
[0090] The difference from Example 1 is that in step (5), the radiation dose of the radiation cross-linking treatment is 50 KGy, and the remaining steps are the same as Example 1.
[0091] Embodiment 11
[0092] The difference from Example 1 is that in step (5), the radiation dose of the radiation cross-linking treatment is 1 KGy, and the remaining steps are the same as Example 1.
[0093] Example 12
[0094] The difference from Example 1 is that in step (5), the radiation dose of the radiation cross-linking treatment is 60 KGy, and the remaining steps are the same as Example 1.
[0095] Embodiment 13
[0096] The difference from Example 1 is that in step (5), the electron beam energy of the irradiation cross-linking treatment is 2 MeV, the electron beam current is 20 mA, and the remaining steps are the same as Example 1.
[0097] Embodiment 14
[0098] The difference from Example 1 is that in step (5), the electron beam energy of the irradiation cross-linking treatment is 3 MeV, the electron beam current is 30 mA, and the remaining steps are the same as Example 1.
[0099] Embodiment 15
[0100] The difference from Example 1 is that in step (3), the resin slurry is coated on the surface of the PET base film layer 10 to obtain a wet film with a thickness of 150 μm, and in step (4), the resin slurry is coated on the surface of the e-PTFE membrane layer to obtain a wet film with a thickness of 150 μm, and the remaining steps are the same as in Example 1; the thickness of the proton exchange membrane obtained in this example is 15 μm.
[0101] Example 16
[0102] The difference from Example 1 is that in step (3), the resin slurry is coated on the surface of the PET base film layer 10 to obtain a wet film with a thickness of 160 μm, and in step (4), the resin slurry is coated on the surface of the e-PTFE membrane layer to obtain a wet film with a thickness of 160 μm, and the remaining steps are the same as in Example 1; the thickness of the proton exchange membrane obtained in this example is 16 μm.
[0103] Comparative Example 1
[0104] The difference from Example 1 is that no cross-linking agent is introduced in step (2), and the remaining steps are the same as Example 1.
[0105] The contact angle test of the resin slurry prepared in all the examples and comparative examples of the present application was carried out using an optical contact angle meter (Bioline, model Theta Lite). The specific test method is: under the conditions of 25°C and 50% RH, the resin slurry is dripped onto the surface of the e-PTFE membrane layer, and the timing is started from the moment when the resin slurry drips onto the surface of the e-PTFE membrane layer, and the test data of the 15th second is recorded.
[0106] The test results are shown in Table 1. When the measured contact angle is ≤30°, it indicates that the resin slurry has a lower surface tension on the surface of the e-PTFE membrane layer, and the lower the contact angle value, the lower the surface tension on the surface of the e-PTFE membrane layer.
[0107] Table 1
[0108] Contact angle (°) Example 1 23.11 Example 2 22.54 Example 3 22.35 Example 4 22.17 Example 5 21.72 Example 6 23.21 Example 7 25.17 Example 8 27.24 Example 9 23.11 Example 10 23.11 Embodiment 11 23.11 Example 12 23.11 Embodiment 13 23.11 Embodiment 14 23.11 Embodiment 15 23.11 Example 16 23.11 Comparative Example 1 88.96
[0109] The proton exchange membranes prepared in all the embodiments and comparative examples of the present application were subjected to tensile strength test, elastic modulus test and conductivity test. (1) Under the conditions of 25°C and 50% RH, the tensile strength test and elastic modulus test were performed using a universal testing machine, wherein the width of the test strip was 6 mm, the clamping spacing was 50 mm, and the tensile rate was 50 mm / min; (2) Under the conditions of 80°C and 80% RH, the conductivity test was performed using a four-electrode probe method, wherein the test sample was a 30 mm×10 mm rectangular.
[0110] The test results are shown in Table 2.
[0111] Table 2
[0112]
[0113] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0114] By comparing Examples 1, 6 to 8 and Comparative Example 1, it can be seen that the introduction of a cross-linking agent having a structure shown in the general formula (I) of the present application when preparing the resin slurry can inhibit the agglomeration of perfluorosulfonic acid resin particles in the solvent, improve the dispersibility and stability of the resin slurry, reduce the surface tension of the resin slurry on the surface of the organic polymer film layer 20, and improve its wetting effect with the base film layer 10 and the organic polymer film layer 20, thereby forming a more uniform and stable membrane layer structure; and the cross-linking agent of the present application can undergo a free radical cross-linking reaction under the radiation cross-linking treatment of step S4, and at the same time combine with the active sites on the perfluorosulfonic acid resin to form a stable cross-linked network, thereby improving the tensile strength and elastic modulus of the proton exchange membrane; at the same time, the presence of the hydrophilic group can also enhance the wettability of the proton exchange membrane, promote the conduction of protons, and thus improve the conductivity of the proton exchange membrane.
[0115] Comparing Examples 1 to 5, the amount of crosslinking agent added in Example 5 is relatively large, so the resin slurry prepared therefrom has a lower surface tension on the surface of the e-PTFE membrane layer. However, according to Table 2, it can be seen that excessive crosslinking agent will cause the mechanical strength and conductivity of the proton exchange membrane to decrease. It can be seen that, compared with other ranges, limiting the weight percentage of the crosslinking agent in the resin slurry to the above range is conducive to increasing the crosslinking density of the first resin layer 31 and the second resin layer 41, thereby facilitating the formation of a more stable crosslinked network structure, and further facilitating the improvement of the mechanical strength and stability of the proton exchange membrane; on the other hand, it is conducive to introducing a more appropriate amount of hydrophilic groups, which is conducive to suppressing the reduction of proton transfer efficiency caused by excessive crosslinking agent, thereby facilitating the improvement of the proton transfer efficiency while improving the mechanical strength of the proton exchange membrane.
[0116] By comparing Examples 1, 9 to 12, it can be seen that, compared with other ranges, limiting the radiation dose of the radiation cross-linking treatment within the above range is beneficial to improving the efficiency of the radiation cross-linking treatment, and is beneficial to inhibiting damage to the membrane layer structure during the radiation cross-linking treatment, thereby helping to improve the mechanical strength and stability of the proton exchange membrane.
[0117] By comparing Examples 1, 13 and 14, it can be seen that, compared with other ranges, limiting the electron beam energy and electron beam current of the radiation cross-linking treatment within the above-mentioned range is beneficial to improving the efficiency of the radiation cross-linking treatment, and is beneficial to inhibiting damage to the membrane layer structure during the radiation cross-linking treatment, thereby helping to improve the mechanical strength and stability of the proton exchange membrane.
[0118] By comparing Examples 1, 15 and 16, it can be seen that, compared with other ranges, limiting the first wet film thickness and the second wet film thickness within the above range is beneficial to obtaining the first resin slurry layer 30 and the second resin slurry layer 40 of appropriate thickness, which is beneficial to suppressing the increase in proton transfer resistance caused by excessive thickness of the first resin slurry layer 30 and the second resin slurry layer 40, thereby helping to improve the mechanical strength and proton transfer efficiency of the proton exchange membrane.
[0119] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a proton exchange membrane, characterized in that: The preparation method comprises: Step S1, mixing perfluorosulfonic acid resin particles, a cross-linking agent and a solvent to obtain a resin slurry; The cross-linking agent is a compound represented by general formula (I): Wherein, R1 is selected from C1-C4 straight chain or branched chain alkylene, or a connecting bond; R2 is selected from hydrogen or a C1-C4 straight or branched alkyl group; n is any integer from 1 to 4; Step S2, applying a portion of the resin slurry to one side surface of the base film layer (10) to obtain a first wet film, covering the surface of the first wet film with a layer of organic polymer film layer (20), and obtaining a first laminated structure after a first drying; the first laminated structure comprises the base film layer (10), the first resin slurry layer (30) and the organic polymer film layer (20) which are sequentially laminated; Step S3, applying another portion of the resin slurry to a surface of the organic polymer film layer (20) away from the base film layer (10) to obtain a second wet film, and obtaining a second laminated structure after a second drying; the second laminated structure comprises the base film layer (10), the first resin slurry layer (30), the organic polymer film layer (20) and the second resin slurry layer (40) which are sequentially laminated; Step S4, under an inert atmosphere, subjecting the second laminate structure to radiation cross-linking treatment, and after completion, peeling off the base membrane layer (10) to obtain the proton exchange membrane; the proton exchange membrane comprises a first resin layer (31), the organic polymer membrane layer (20) and a second resin layer (41) which are sequentially stacked.
2. The method for preparing a proton exchange membrane according to claim 1, characterized in that: The R1 is methylene, ethylene, or connection key; Preferably, n is 1 or 2, and R2 is hydrogen; Preferably, n is 3, and R2 is a C1-C4 straight-chain alkyl group, preferably a methyl group or an ethyl group; Preferably, n is 4, and R1 is a methylene group.
3. The method for preparing a proton exchange membrane according to claim 1 or 2, characterized in that: The cross-linking agent is selected from one or more of the following compounds:
4. The method for preparing a proton exchange membrane according to any one of claims 1 to 3, characterized in that: The weight percentage of the cross-linking agent in the resin slurry is 1 to 10 wt %; Preferably, the weight ratio of the perfluorosulfonic acid resin particles to the solvent is 1:(1-100); Preferably, the weight ratio of the perfluorosulfonic acid resin particles to the cross-linking agent is (1-30):1; Preferably, the ion exchange equivalent of the perfluorosulfonic acid resin particles is 500 to 1500 g / mol, and the average particle size is 50 to 500 mm; Preferably, the solvent is selected from water and / or alcohol solvents; more preferably, the alcohol solvent is selected from one or more of the group consisting of ethanol, isopropanol, n-propanol, n-butanol and n-hexanol.
5. The method for preparing a proton exchange membrane according to claim 4, characterized in that: The viscosity of the resin slurry is 10 to 100 mPa·s; Preferably, in step S2, the thickness of the first wet film is 70-150 μm; Preferably, in step S3, the thickness of the second wet film is 70-150 μm.
6. The method for preparing a proton exchange membrane according to any one of claims 1 to 5, characterized in that: The organic polymer film layer (20) is a porous film; Preferably, the organic polymer film layer (20) has a porosity of 50-90%, an average pore size of 80-300 μm, and a thickness of 4-15 μm; Preferably, the base film layer (10) has a thickness of 50 to 200 μm; Preferably, the material of the organic polymer film layer (20) is expanded polytetrafluoroethylene; Preferably, the material of the base film layer (10) is selected from one or more of the group consisting of polyethylene terephthalate, polyimide and polyphenylene sulfide.
7. The method for preparing a proton exchange membrane according to claim 6, characterized in that: In the step S4, the radiation cross-linking treatment is performed using electron beams or gamma rays; Preferably, the electron beam is used to perform the radiation cross-linking treatment, the radiation dose of the radiation cross-linking treatment is 1 to 50 KGy, the electron beam energy is 0.8 to 2 MeV, and the electron beam current is 5 to 20 mA.
8. The method for preparing a proton exchange membrane according to claim 7, characterized in that: In the step S1, the mixing temperature is 25 to 100° C. and the mixing time is 0.5 to 5 hours; Preferably, stirring is performed during the mixing process, and the stirring rate is 200 to 1000 rpm; Preferably, in step S2, the first drying temperature is 60-200° C. and the time is 1-20 min; Preferably, in step S3, the second drying temperature is 60-200° C., and the time is 1-20 min.
9. A proton exchange membrane, characterized in that: The proton exchange membrane is prepared by the method for preparing a proton exchange membrane according to any one of claims 1 to 8; the proton exchange membrane comprises a first resin layer (31), an organic polymer membrane layer (20) and a second resin layer (41) which are stacked in sequence; the proton exchange membrane has a tensile strength of 49 to 76 MPa in the transverse direction, an elastic modulus of 418 to 873 MPa in the transverse direction, a tensile strength of 50 to 78 MPa in the longitudinal direction, an elastic modulus of 446 to 880 MPa in the longitudinal direction, and an electrical conductivity of 0.091 to 0.251 S / cm; Preferably, the proton exchange membrane has a thickness of 8 to 15 μm.
10. Use of the proton exchange membrane according to claim 9 in a proton exchange membrane fuel cell.
Citation Information
Patent Citations
Process for preparing novel crosslinkable polyarylether ketone sulfonated film
CN1482161A